Assessing the impact of the FIFA World CupTM Germany 2006 - Some methodological and empirical reflections - Gerd Ahlert (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2007)
Big tourist events have undoubtedly a considerable economic dimension. The spectators of these events buy entrance tickets, use the traffic system and take advantage of the services of the restaurant and hotel business. The organisers invest in the extension of tourism facilities and traffic networks and provide the means of production for the smooth running of the event. Especially big sports events are important advertising media. Furthermore the rights of television broadcast and the contributions of sponsors are an important source of finance. For the respective region, carrying out such an event often means a strain e. g. regarding the volume of traffic. At the same time the event may lead to a lasting improvement of the regional infrastructure. Last but not least the regions' image will be improved by carrying out the event only due to the media coverage. Assessing the impact of tourist events is rather difficult because such events have always significant regional economic effects but not necessarily appreciable overall economic effects (comp. Ahlert, 2001, p. 116). Only in the case of international tourist events their spending determine definitely positive the outcome on regional as well as on national economic level, but especially in the case of such major international tourist events the positive macroeconomic effects are associated with substantial external effects. The paper gives an overview of various economic studies - cost-benefit analysis (Rahmann et al., 1998; Kurscheidt, Rahmann, 1999), impact analysis (Ahlert, 2000; Meyer, Ahlert, 2002; Ahlert, 2005) and regional studies (Meyer, Ahlert, 2000; Wegweiser GmbH, 2004) which have been prepared in Germany in the past to identify the potential tangible and intangible effects of the FIFATM World Cup 2006. It explains the strength and weakness of the different approaches and how these different types of analysis can perfectly fit together for identifying the potential regional, sectoral and national socioeconomic effects. Besides that the paper shows what kind of mistakes respective misinterpretation of such studies and their results can be frequently observed.
Keywords: 330